Rectal dexmedetomidine in rats: evaluation of sedative and mucosal effects - Hanci,Volkan (2015)
BACKGROUND AND OBJECTIVES: In this study, we investigated the anesthetic and mucosal effects of the rectal application of dexmedetomidine to rats. METHODS: Male Wistar albino rats weighing 250-300 g were divided into four groups: Group S (n = 8) was a sham group that served as a baseline for the normal basal values; Group C (n = 8) consisted of rats that received the rectal application of saline alone; Group IPDex (n = 8) included rats that received the intraperitoneal application of dexmedetomidine (100 µg kg-1); and Group RecDex (n = 8) included rats that received the rectal application of dexmedetomidine (100 µg kg-1). For the rectal drug administration, we used 22 G intravenous cannulas with the stylets removed. We administered the drugs by advancing the cannula 1 cm into the rectum, and the rectal administration volume was 1 mL for all the rats. The latency and anesthesia time (min) were measured. Two hours after rectal administration, 75 mg kg-1 ketamine was administered for intraperitoneal anesthesia in all the groups, followed by the removal of the rats' rectums to a distal distance of 3 cm via an abdominoperineal surgical procedure. We histopathologically examined and scored the rectums. RESULTS: Anesthesia was achieved in all the rats in the Group RecDex following the administration of dexmedetomidine. The onset of anesthesia in the Group RecDex was significantly later and of a shorter duration than in the Group IPDEx (p < 0.05). In the Group RecDex, the administration of dexmedetomidine induced mild-moderate losses of mucosal architecture in the colon and rectum, 2 h after rectal inoculation. CONCLUSION: Although 100 µg kg-1 dexmedetomidine administered rectally to rats achieved a significantly longer duration of anesthesia compared with the rectal administration of saline, our histopathological evaluations showed that the rectal administration of 100 µg kg-1 dexmedetomidine led to mild-moderate damage to the mucosal structure of the rectum.